Touching, devotional practices, and visionary experience in the late Middle Ages - Carrillo-Rangel, David; Nieto-Isabel, Delfi I.; Acosta-Garcia, Pablo (Palgrave Macmillan, 2019)
This book addresses the history of the senses in relation to affective piety and its role in devotional practices in the late Middle Ages, focusing on the sense of touch. It argues that only by deeply analysing this specific context of perception can the full significance of sensory religious experience in the Late Middle Ages be understood. Considering the centrality of the body to medieval society and Christianity, this collection explores a range of devotional practices, mainly relating to the Passion of Christ, and features manuscripts, works of devotional literature, art, woodcuts and judicial records. It brings together a multidisciplinary group of scholars to offer a variety of methodological approaches, in order to understand how touch was encoded, evoked and purposefully used. The book further considers how touch was related to the medieval theory of perception, examining its relation to the inner and outer senses through the eyes of visionaries, mystics, theologians and confessors, not only as praxis but from different theoretical points of view. While considered the most basic of spiritual experience, the chapters in this book highlight the all-pervasive presence of touch and the significance of ?affective piety? to Late Medieval Christians.0Chapter 3: Drama, Performance and Touch in the Medieval Convent and Beyond is Open Access under a CC BY 4.0 license at link.springer.com